2022
DOI: 10.1371/journal.pone.0266375
|View full text |Cite
|
Sign up to set email alerts
|

Rapid screening of SARS-CoV-2 infection: Good performance of nasopharyngeal and Nasal Mid-Turbinate swab for antigen detection among symptomatic and asymptomatic individuals

Abstract: Although the nasopharyngeal swab (NPS) is considered the gold standard for the diagnosis of the SARS-CoV-2 infection, the Nasal Mid-Turbinate swab (NMTS) is often used due to its higher tolerance among patients. We compared the diagnostic performance of the NPS and the NMTS for the Panbio™ COVID-19 antigen-detecting rapid diagnostic test (Ag-RDT). Two hundred and forty-three individuals were swabbed three times by healthcare professionals: a NMTS and a NPS specimen for the Ag-RDT and an oropharyngeal swab for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
(56 reference statements)
1
6
1
Order By: Relevance
“…However, users should be mindful of the RDT kits’ limitations. Studies have found that screening asymptomatic people has a low sensitivity [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, users should be mindful of the RDT kits’ limitations. Studies have found that screening asymptomatic people has a low sensitivity [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the 49 studies on nasal swabs containing 79,073 samples [ [2] , [3] , [4] , 6 , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] ], all of them were published between 2021 and 2022, and twenty-one studies were conducted in the USA [ 12 , 14 , 15 , 18 , 21 , 22 , [25] , [26] , [27] , [32] , [33] , [34] , [35] , 39 , 44 , 45 , [47] ...…”
Section: Resultsmentioning
confidence: 99%
“…Currently, nasopharyngeal swabs and oropharyngeal swabs are the recommended standard sampling techniques in RAT for SARS-CoV-2 detection, yet these have some limitations such as the complexity of collection. Nasal swabs, less invasive than nasopharyngeal swabs, represent a more comfortable approach to sampling [ 5 ]. They do not require skilled professionals, providing the basis for their use as a self-sampling technique [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“… In patients with signs and symptoms compatible with COVID-19 of more than 7 days-onset, we suggest the use of laboratory-based NAAT versus rapid antigen detection testing for the diagnosis of COVID-19. Weak against Very low [ 7 , 26 , 106 , 119 , 126 , 129 , 135 , [137] , [138] , [139] , [140] , 28 , 37 , 60 , 61 , 65 , 78 , 81 , 100 ] 17 In children<12 years with signs and symptoms compatible with COVID-19, should rapid antigen detection testing be used, compared with standard NAAT (commercial and/or in house) for diagnosis of COVID-19? In children <12 years old with signs and symptoms compatible with COVID-19, we suggest the use of laboratory-based NAAT versus rapid antigen detection testing for the diagnosis of COVID-19.…”
Section: Questions Addressed By the Guideline Updatementioning
confidence: 99%